2022
DOI: 10.1097/md.0000000000030651
|View full text |Cite
|
Sign up to set email alerts
|

Effects of goal-oriented nursing intervention on postpartum depression

Abstract: This retrospective study aimed to explore the effects of goal-oriented nursing intervention (GONI) on postpartum depression (PPD). We retrospectively analyzed the medical records of 72 women with PPD. They were allocated to a treatment group (n = 36, exercise plus GONI) or a control group (n = 36, exercise). Patients in both groups received a total of 3 months of treatment. Outcomes included the 17-item Hamilton Rating Scale for Depression (HAMD-17) total score, HAMD-17 response rate (≥50% score reduction), HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Some studies have shown that in the community comprehensive home intervention for postpartum depressed pregnant women, family members are guided to actively participate, 29 which can effectively relieve the symptoms of PPD, improve the bad psychology of pregnant women, improve the quality of life and restore their physical and mental health. 30 However, community providers have focused primarily on maternal health issues and the cooperative interaction relationship between community service providers and family members needs further research. Two types of social interactions, collaboration and social support have been identified as particularly important in a caregiving context.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that in the community comprehensive home intervention for postpartum depressed pregnant women, family members are guided to actively participate, 29 which can effectively relieve the symptoms of PPD, improve the bad psychology of pregnant women, improve the quality of life and restore their physical and mental health. 30 However, community providers have focused primarily on maternal health issues and the cooperative interaction relationship between community service providers and family members needs further research. Two types of social interactions, collaboration and social support have been identified as particularly important in a caregiving context.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Moreover, Mundorf et al 28 believe that strengthening the relationship between community health workers and family members during perinatal period can affect PPD outcomes. Some studies have shown that in the community comprehensive home intervention for postpartum depressed pregnant women, family members are guided to actively participate,29 which can effectively relieve the symptoms of PPD, improve the bad psychology of pregnant women, improve the quality of life and restore their physical and mental health 30. However, community providers have focused primarily on maternal health issues and the cooperative interaction relationship between community service providers and family members needs further research.…”
Section: Introductionmentioning
confidence: 99%